The Effects Of Tumor Localization On Small Cell Lung Cancer And Its Association With Prognosis - Sertan Bulut; Deniz Çelik (Acta Medica Alanya)
Aim: Lung cancer is classified as non-small cell lung cancer (NSCLC) and small-cell lung cancer (SCLC) as pathological subtypes. SCLC is associated with a significantly short life expectancy, and it constitutes 10-15% of all lung cancers. Previous studies showed that lung cancer is mostly dominated by the upper lobe and is more common in the right lung than in the left. The main aim of this study is to analyze the localization of the tumor in the right and left lung in aggressive and malignant SCLC patients by comparing it with determinants such as anatomical features, demographic features, laboratory features, including the association with peripheral-central localizations, especially overall survival.Methods: There were four hundred forty-six lung cancer patients diagnosed in a chest diseases clinic in a tertiary training and research hospital between 31.03.2014 and 31.03.2020. Of these, twenty percent (n=90) were diagnosed as SCLC. Among ninety patients, six were excluded from the study due to incomplete medical SCLC records, and finally, eighty-four patients with SCLC were included in the study.Results: We classified eighty-four patients into two groups as right and left lung localized SCLC and analyzed all the data. We found that the left lung tumor group had the more extensive-stage disease and had significantly high CRP levels (p=0.027, p=0.045, respectively). When we analyzed the data such as demographic characteristics, diagnostic methods, overall survival, treatment characteristics, stage characteristics, anatomical features of the right and left tumor groups, we found that there were no significant differences.We use univariate and then multivariate analysis for survival. We found that being sixty-five years old and over (p=0.014), high CRP levels (p=0.016), having centrally localized tumors (p=0.01), having poor performance status (p<0.0001), and having no treatment for primary cancer (p=0.001) were associated with worse survival.Conclusion: Primary treatment of SCLC patients should start promptly. We found that the central location of the tumor as anatomical localization may be associated with worse survival. Also, we found that the left lung tumor group had the more extensive-stage disease and had significantly high CRP levels. Being sixty-five years old and over, high CRP levels, having poor performance status, and having no treatment for primary cancer were significantly associated with worse survival.